Kontroversi Mahar Perkawinan Dengan Hafalan Al-Qur’an Perspektif Hukum Islam - Rozak, Fakih Abdul; Maritsa Rahmah; Nur Afifah (Tasamuh: Jurnal Studi Islam, 2024)
The dowry or maskawin is the property given by the groom to the bride at the time of the wedding. The forms of dowry used are also varied, such as cash, shares, prayer equipment, even memorizing the Koran. The phenomenon of giving a wedding dowry in the form of memorizing the Koran is often heard in society. Sometimes, such a dowry is a request from the bride to her future husband. It is feared that many people will misunderstand Sahl bin Sa'ad's hadith about the man whom Rasulullah SAW married with a dowry from memorizing the Koran. A review of Islamic law and the theory of maqasid al-syariyah is very appropriate to use in determining the legal certainty of this phenomenon. This research is a qualitative literature review (library research) with data collected using documentary methods and analyzed using descriptive qualitative analysis techniques. The results of this research are that the law of giving a wedding dowry in the form of memorizing the Koran is permissible, because it is considered not to conflict with Islamic law. The dowry for memorizing the Koran is also a manifestation of a man's efforts to implement the principles and objectives of Islamic law, namely maintaining honor. The wisdom aspect of the background of giving a dowry in the form of memorizing the Koran is very harmonious with the aim of prescribing a dowry for someone who wants to marry a woman.